Benjamin Friedman on Arabs in Israeli literature - H. F. van Rooy (Literator, 1982)
Benjamin Friedman was working on a thesis for his doctorate at the University of Potchefstroom when he passed away in 1979. He was immensely interested in the way the Israeli Hebrew writers pictured the Arabs in their fiction and had done a massive amount of research when he died. He was therefore unable to complete his research and to present his views in a complete study. He did, however, leave a manuscript which reflected his research and conclusions. This was edited by his family' and the University of Potchefstroom gave recognition to his work by awarding him the degree M.A. posthumously. The writer of this paper added a chapter to Mr . Friedman’s manuscript, summarising his main views on the topic. Menahem D. Rotshtein’s paper on this same subject prompted me to present Benjamin Friedman’s view on this important subject, in aid of further research and discussion.